2014
DOI: 10.1177/1040638714553294
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystic adenocarcinoma and pancreatic insulinomas in a goat

Abstract: Abstract.A 13-year-old female Boer goat with a history of chronic arthritis and recurrent episodes of recumbency, increased serum gamma-glutamyl transferase, and complete inability to stand was submitted for necropsy. Gross changes included the presence of a white, firm, smooth, 6 cm × 4 cm × 3 cm mass that diffusely expanded and partially effaced the gall bladder and infiltrated the adjacent hepatic parenchyma. On cut surface, the mass was pale yellow and had small, irregular, dark yellow areas. Scattered thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Four of the 13 (31%) goats diagnosed with skin SCC were Saanens, though Saanens were not overrepresented in this group (P = .20). Other breeds included Cashmere (n = 3), mixed breed (2), Nubian (1), Nigerian Dwarf (1), Boer (1), and Tennessee Fainting (1). The majority of goats with SCC (12/14 [86%]) had a white hair coat.…”
Section: Skin Neoplasiamentioning
confidence: 99%
See 2 more Smart Citations
“…Four of the 13 (31%) goats diagnosed with skin SCC were Saanens, though Saanens were not overrepresented in this group (P = .20). Other breeds included Cashmere (n = 3), mixed breed (2), Nubian (1), Nigerian Dwarf (1), Boer (1), and Tennessee Fainting (1). The majority of goats with SCC (12/14 [86%]) had a white hair coat.…”
Section: Skin Neoplasiamentioning
confidence: 99%
“…However, unlike in small-animal or equine medicine in which neoplastic diseases are better understood, there are limited published data on clinical presentation, treatment, or outcome in goats with neoplasia.Specific caprine neoplasms have been described in case reports and a limited number of retrospective analyses. [1][2][3][4][5][6] Yau and Rissi 7 reported a case of a goat with cholecystic adenocarcinoma and insulinomas, and 2 cases of leiomyosarcoma in related Saanen does have been described. Hill et al 6 reported the clinical signs, signalment, treat-…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Insulinoma has been reported in various animal species including dogs, cats, ferrets, horses, cows, and a goat. 7,8,25 We found no reports of insulinoma in sheep in a search of Google, PubMed, and Scopus. Insulinomas are classified as benign or malignant depending on the behavior of the tumor.…”
mentioning
confidence: 94%
“…7 Although the incidence of insulinoma in ruminants is rarer than in companion animals, insulinoma has been described in slaughtered adult cows 8 and an aged goat. 25 We retrieved no ovine cases of MEN or insulinoma in a search of Google, PubMed, and Scopus, suggesting that those conditions have not been reported in sheep.…”
mentioning
confidence: 99%